A diagnostic model for serious COVID-19 infection among older adults in Shanghai during the Omicron wave - Bao, Suxia; Lu, Guanzhu; Kang, Yaoyue; Zhou, Yuanyuan; Wang, Yuhuan; Yan, Lei; Yin, Donglin; Bao, Yujie; Yuan, Xiaoling; Xu, Jie (Frontiers in Medicine, 2022)
Background: The Omicron variant is characterized by striking infectivity and antibody evasion. The analysis of omicron variant BA.2 infection risk factors was very limited among geriatric individuals, which was correlated with the improvement of the public health system and the reduction of mortality. Therefore, our research investigated BA.2 infection risk factors for discriminating severe/critical patients from mild/moderate patients among geriatric individuals. Methods: Baseline characteristics of enrolled geriatric Omicron infections (aged over 60) were analyzed. A logistic regression analysis was conducted to evaluate factors correlated with severe/critical patients. A receiver operating characteristic (ROC) curve was constructed for predicting variables to discriminate mild/moderate patients from severe/critical patients. Results: A total of 595 geriatric patients older than 60 years were enrolled in this study. Lymphocyte subsets were significantly downregulated, and white B cells (WBCs) and D-Dimer were highly upregulated with disease progression from a mild/moderate state to a severe/critical state. Univariate and multivariate logistic regression analysis analyses identified a panel of WBCs, CD4+ T cells and D-Dimer values that were correlated with good diagnostic accuracy for discriminating mild/moderate patients from severe/critical patients with an area under the curve of 0.962. Conclusion: Some key baseline laboratory indicators changed with disease development. A panel was identified that was able to discriminate mild/moderate patients from severe/critical patients, suggesting that the panel could serve as a potential biomarker to enable physicians to provide timely medical services in clinical practice.